The lichen genus Villophora (Teloschistaceae, Ascomycota) - Sochting, Ulrik; Sogaard, Majbrit Zeuthen; Sancho, Leo Garcia; Arup, Ulf (The Lichenologist, 2021)
The Southern Hemisphere lichen genus Villophora in subfamily Teloschistoideae is analyzed based on DNA sequence data. Six species are described, five of which are new to science: V. darwiniana and V. wallaceana grow on lignum and bark in southern Patagonia and Tierra del Fuego; V. onas and V. patagonica are lichenicolous or saxicolous on rocks in southern Patagonia; V. rimicola is saxicolous in Antarctica. Based on a three-gene DNA analysis, Tayloriellina is shown to be closely related to Villophora, and Tayloriellina microphyllina is established as a new combination. A key is provided to all species of the two genera. Raesaeneniana maulensis is combined into Villophora.